1987
DOI: 10.1159/000124740
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sexual Differentiation of the Hypothalamus in the Differential Effect of the Serotoninergic System on LH in Prepubertal Male and Female Rats

Abstract: 5-hydroxytryptophan (5-HTP), a serotonin precursor, has been shown to induce LH release in female but not in male rats at 16, 18 and 20 days of age. The purpose of this study was to investigate the role of neonatal gonadal hormones on 5-HTP-induced LH release in male and female rats of 16 and 20 days of age. The following groups of rats were studied (a) control females, (b) androgenized females, (c) control males, and (d) castrated males. Androgenization and castration were performed within 48 h of birth. 5-HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…According to previous results [13][14][15], LHRH neurons would also change their responsiveness to 5-HT during sexual maturation in female rats. This change was not observed in males.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…According to previous results [13][14][15], LHRH neurons would also change their responsiveness to 5-HT during sexual maturation in female rats. This change was not observed in males.…”
Section: Discussionmentioning
confidence: 57%
“…In immature female rats 5-hydroxytryptophan (5-HTP), a 5-HT precursor that increases hypothalamic concentra tions of this neurotransmitter, induces LH release at 16, 18 and 20 days of age; this effect is no longer observed in 26-day-old rats [13][14][15]. In immature female rats, 5-HT is likely to have an inhibitory' action on LH secretion [13].…”
mentioning
confidence: 99%
“…It has been previously demonstrated that the administration of 5-HTP induces LH release in prepubertal female rats [11][12][13], but not in male rats. These results demonstrate that in prepubertal rats there are sexual differences in the LH release response to 5-HTP.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, 5-hydroxytryptophan (5-HTP) induces LH release in female prepubertal rats, but not in males [11]. We proposed that the sexual difference in the LH response to 5-HTP might be asso ciated with the regulatory action of serotonin on the cyclic hypothalamic control of gonadotrophin secretion [ 13].1 Supported by Grants from the Consejo Nacional de Investigaciones Científicas y Técnicas and from the University of Buenos Aires, Repú blica Argentina. Received: July 6, 1988 Accepted after revision: February 10, 1989 In adult male rats serotonin modifies FSH secretion when injected into the third ventricle of the brain having an inhibitory effect on this pituitary gonadotrophin [9].…”
mentioning
confidence: 99%
“…Nevertheless it is interesting to note in this respect that several neuroendocrine mechanisms of gonadotropin con trol change during sexual development. For instance 5-HTP in duces LH release in prepubertal but not in peripubertal or adult rats [10,11] and catecholamines inhibit gonadotropin secretion in prepubertal but stimulate these hormones in peripubertal and adult rats [12]. These modifications in the neuroendocrine control of gonadotropin secretion are related to the onset of sexual maturation [10][11][12].…”
Section: Discussionmentioning
confidence: 99%